Factors Affecting Uzbek Students' Prewriting Investment at a South Korean University - Jiayu Zhang; Jungyin Kim (MDPI AG, 2024)
This ethnographic multiple-case study, grounded in the theory of investment, examines the prewriting practices of three Uzbekistani male undergraduates in an English essay writing class at a South Korean University. It aims to identify the symbolic resources they perceive as attainable through investment and to elucidate the factors shaping this investment. Utilizing a qualitative approach, which is appropriate for capturing the nuanced experiences and perceptions of individual learners, data were collected through interviews, classroom observations, and an analysis of teaching documents. This study finds that these students primarily seek three symbolic resources: language skills, educational access, and social networks. Their pursuit of these resources is significantly influenced by their academic aspirations for graduate school and the pattern of prewriting discussions in the classroom. Individual perceptions and priorities uniquely shape the impact of these factors on each student's investment. The findings suggest that educators, by understanding the diverse perceptions of symbolic resources within limited instructional time, can tailor pedagogical strategies to effectively address students' needs and foster a more engaging learning environment.